Decidual macrophage derived MMP3 contributes to extracellular matrix breakdown in spiral artery remodeling in early human pregnancy. (March 2022) - Pan, Yue; Yang, Li; Chen, Danyang; Hou, Huomei; Zhang, Min; Chen, Miaojuan; Ning, Fen; Lu, Qinsheng; Zhao, Minguan; Li, Li; Lash, Gendie E.
Abstract: Remodeling of the uterine spiral arteries is required for a successful pregnancy. This process requires the co-ordinated activity of a number of different cell types including uterine natural killer cells, decidual macrophages, extravillous trophoblast cells, vascular smooth muscle cells and endothelial cells. We have previously demonstrated that decidual macrophages facilitate breakdown of fibronectin and laminin in a model of spiral artery remodeling. The aim of the current study was to determine which matrix metalloproteinases (MMPs) decidual macrophages express and play roles in extracellular matrix (ECM) breakdown in vascular remodeling. Decidual macrophages were isolated from first trimester decidua and cultured for 24 h to obtain conditioned medium. MMP secretion was assessed by a membrane based array and immunohistochemistry of decidual sections. In addition, the chorionic plate artery (CPA) model was used with decidual macrophage conditioned medium, with and without a MMP3 inhibitor and ECM protein expression assessed using quickscore. The decidual macrophages secreted a wide range of MMPs, with MMP3 being the most predominant. Co-localization of MMP3 to decidual macrophages was confirmed by immunohistochemistry. Decidual macrophage conditioned medium facilitated breakdown of laminin and fibronectin in the CPA model, an effect that was abrogated by the MMP3 inhibitor. These data further support the role of decidual macrophages in tissue remodeling in the first trimester of pregnancy. An alteration in their numbers or phenotype would impact spiral artery remodeling and contribute to the etiology of a number of complications of pregnancy. Highlights: Decidual macrophages secrete a wide range of matrix metalloproteinases. Decidual macrophages facilitate ECM breakdown in vascular remodeling. Decidual macrophage facilitated vascular ECM breakdown is mediated by MMP3.